Familial Non-autoimmune Hyperthyroidism in Family Members Across Four Generations Due To a Novel Disease-causing Variant in The Thyrotropin Receptor Gene - Malej, A (Balkan J Med Genet, 2021)
Activating disease-causing variants in the thyrotropin-receptor (TSHR) gene are associated with familial or sporadic congenital non-autoimmune hyperthyroidism. Familial non-autoimmune hyperthyroidism (FNAH) is a rare form of hyperthyroidism with 41 families reported so far in the TSHR gene mutation database. We present clinical and genetic features of 11 patients with FNAH across four generations of a Slovenian family. They all developed clinical features of hyperthyroidism but did not show characteristics of autoimmune hyperthyroidism. Members of the initially diagnosed generation were diagnosed as hyperthyrotic after they developed cardiac complications (rhythm disorders, thromboembolic events, cardiac insufficiency), while patients in the younger generations were diagnosed earlier, and consequently, early cardiovascular complications were less frequent. All patients had a novel heterozygous TSHR variant NP_ 000360.2: p.Met453Val (NM_000369.2: c.1357A>G) predicted to be pathogenic. Therefore, besides expending the mutational spectrum of the activating TSHR variants in FNAH, our experience with this multi-generation family confirms the need for early diagnosis and appropriate treatment of FNAH.